Real world use of a neurophysiology service for the differential diagnosis of hyperkinetic movement disorders. (February 2020) - Gandhi, Sacha E.; Silverdale, Monty A.; Mercer, Deborah; Marshall, Andrew G.; Kobylecki, Christopher
Abstract: Introduction: Clinical neurophysiology constitutes a potentially useful aid in differentiating hyperkinetic movement disorders (HMD). Parameters including presence of a Bereitschaftspotential on back-averaged electroencephalography (EEG) have been demonstrated to help distinguish between these disorders. In 2008, a Movement Disorder neurophysiology service was established in Greater Manchester to aid in the diagnostic process. Methods: We retrospectively reviewed records of patients with HMD who underwent EEG back-averaging through this service from January 2009 until January 2018. The aim was (i) to characterise the clinical features of our patient cohort and (ii) to determine how frequently neurophysiological testing altered the final diagnosis. Results: A total of 39 patients (23 females, 16 males), with a mean age at onset of 42.6 years and mean disease duration of 2.0 years underwent neurophysiological examination. The clinical diagnosis was changed in 16 cases (41%) and refined in a further seven. Distractibility ( P  = 0.001), variability ( P  = 0.002), the presence of a Bereitschaftspotential ( P  < 0.0001), and electromyography burst duration > 300 ms ( P  = 0.012) were more frequent in those with an eventual diagnosis of functional movement disorder (n = 24) compared to other HMDs (n = 15). Conclusion: Neurophysiology is an invaluable adjunct in complex HMD, altering the diagnosis and treatment options for a significant proportion of patients. Our data also demonstrate, consistent with previous studies, that the majority of patients referred for jerky HMDs to a tertiary movement disorder service have a functional movement disorder. Highlights: We evaluated the effect of assessment for a Bereitschaftspotential in patients referred for hyperkinetic movement disorders. The clinical diagnosis was altered in 41% following neurophysiological assessment. Movement disorder neurophysiology assessment is an invaluable adjunct to clinical assessment.